2000
DOI: 10.1097/00001648-200011000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Are Schizophrenia or Antipsychotic Drugs a Risk Factor for Cataracts?

Abstract: Lens changes and ocular disturbances have been reported in conjunction with the use of antipsychotic drugs. We estimated the incidence rate of a clinical diagnosis of cataract in patients with a psychotic disorder, schizophrenia, and compared it with the rate in the general population. Among the schizophrenic patients, we also examined the role of dose and duration of antipsychotic drugs on the risk of cataract development. We followed up two cohorts of patients 30-85 years of age who were included in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 11 publications
1
23
0
2
Order By: Relevance
“…However, the validity of a recorded diagnosis of cataract in the GPRD has been found to be high (94%) 22 and we were able to ensure some uniformity in diagnostic pattern by matching cases and controls on the general practice used. In spite of this, one of the major challenges facing epidemiological research of cataract is the problem of case ascertainment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the validity of a recorded diagnosis of cataract in the GPRD has been found to be high (94%) 22 and we were able to ensure some uniformity in diagnostic pattern by matching cases and controls on the general practice used. In spite of this, one of the major challenges facing epidemiological research of cataract is the problem of case ascertainment.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of cataract was confirmed by hospital consultant ophthalmologists and the information forwarded to the general practitioner who records this in the medical records. 22 The date of diagnosis was referred to as the index date. Cases were required to have at least 180 days of observation prior to the index date.…”
Section: Methodsmentioning
confidence: 99%
“…Certain AAP may be associated with an increased risk of ocular lens opacities. An epidemiologic study that used the UK General Practice Research Database did not find an overall increase in the risk for cataracts among patients treated with antipsychotics (41).…”
Section: Cataractmentioning
confidence: 93%
“…The GPRD is a computerized database comprising the medical records of more than 10 million UK patients registered with a primary care physician. Previous epidemiological studies based on GPRD data have shown that it can be used to study patients with MS, 22 cataract, 23 and longitudinal exposure to oral GCs. 24,25 Our study was approved by the Independent Scientific Advisory Committee (ISAC) of the Medicines and Healthcare Product Regulatory Agency (MHRA) of the United Kingdom, protocol number 09_098.…”
Section: Data Sourcementioning
confidence: 99%